# Continuity??? Watch

Announcements

Page 1 of 1

Go to first unread

Skip to page:

This discussion is closed.

I have NO idea how to do this question...

Let

h:

k:

Suppose that h(x) = k(x) for every rational number x.

Prove that h and k must be identically equal.

[can assume that for every real number y, there exists a sequence of irrational numbers (tn) tending to y as n->infinity and sequences of rational numbers (rn) and (sn) both tending to y as n->infinity with sn <= y <= rn]

Let

h:

**R**->**R**be continuous andk:

**R**->**R**be monotonic increasing.Suppose that h(x) = k(x) for every rational number x.

Prove that h and k must be identically equal.

[can assume that for every real number y, there exists a sequence of irrational numbers (tn) tending to y as n->infinity and sequences of rational numbers (rn) and (sn) both tending to y as n->infinity with sn <= y <= rn]

0

Report

#2

Fix any real number y.

Let (s_n) and (r_n) be rational sequences such that

(i) s_n <= y <= r_n for all n,

(ii) s_n -> y as n -> infinity,

(iii) r_n -> y as n -> infinity.

By (i) and the monotone increasing property of k,

k(s_n) <= k(y) <= k(r_n) for all n . . . . . (1)

Putting k(s_n) = h(s_n) and k(r_n) = h(r_n) into (1),

h(s_n) <= k(y) <= h(r_n) for all n . . . . . (2)

Since h is continuous at y, it follows from (ii) and (iii) that h(s_n) -> h(y) and h(r_n) -> h(y) as n -> infinity. So (2) says that k(y) is sandwiched between two functions of n, each of which tends to h(y) as n -> infinity. So k(y) = h(y).

Let (s_n) and (r_n) be rational sequences such that

(i) s_n <= y <= r_n for all n,

(ii) s_n -> y as n -> infinity,

(iii) r_n -> y as n -> infinity.

By (i) and the monotone increasing property of k,

k(s_n) <= k(y) <= k(r_n) for all n . . . . . (1)

Putting k(s_n) = h(s_n) and k(r_n) = h(r_n) into (1),

h(s_n) <= k(y) <= h(r_n) for all n . . . . . (2)

Since h is continuous at y, it follows from (ii) and (iii) that h(s_n) -> h(y) and h(r_n) -> h(y) as n -> infinity. So (2) says that k(y) is sandwiched between two functions of n, each of which tends to h(y) as n -> infinity. So k(y) = h(y).

0

Report

#4

Is the result still true if we replace the assumption that h is continuous with the assumption that it is monotone increasing? Give a proof or counterexample. Rep for the first correct answer!

0

Report

#5

(Original post by

Is the result still true if we replace the assumption that h is continuous with the assumption that it is monotone increasing? Give a proof or counterexample. Rep for the first correct answer!

**Jonny W**)Is the result still true if we replace the assumption that h is continuous with the assumption that it is monotone increasing? Give a proof or counterexample. Rep for the first correct answer!

h(x)

= {x if x < pi,

= {4 if x = pi

= {x+2 if x > pi

k(x)

= {x if x < pi,

= {5 if x = pi,

= {x+2 if x>pi

Then h(x) = k(x) except at the irrational pi

0

X

Page 1 of 1

Go to first unread

Skip to page:

new posts

Back

to top

to top